ANGKA KEJADIAN POST OPERATIVE NAUSEA AND VOMITING (PONV) PADA PASIEN SECTIO CAESAREA (SC) METODE ENHANCED RECOVERY AFTER CAESAREAN SURGERY (ERACS) DI RS HERMINA PADANG BULAN SEPTEMBER-OKTOBER TAHUN 2023 - Anita Darmayanti; Syabina Oxania Razak; Bun Yurizali (Yayasan Nusantara Hasana Berdikari, 2023)
Sectio Caesarea (SC) is delivery by making an incision in the abdomen and uterus. The Enhanced Recovery After Caesarean Surgery (ERACS) method is an effective way to reduce length of stay by reducing post-SC side effects.One of the unpleasant effects after surgery is Postoperative Nausea & Vomiting (PONV). The purpose of this study is to determine the incidence of PONV in SC patients using the ERACS method at Hermina Hospital Padang. The type of this research was descriptive observational research with survey method that used primary data through direct interviews in the recovery room of Hermina Hospital Padang with sample size of 77 respondents. Based on the results from the analysis of 77 respondents, it was found that the highest maternal age was 20-35 years, as many as 70 people (90.9%) with a history of previous PONV, it was found that respondents with no previous PONV history were more, as many as 71 people (92.2%) and multiparous mothers were more than primiparous, as many as 50 people (64.9%). The highest incidence of PONV in SC patients using the ERACS method at Hermina Hospital Padang was degree 0 or no nausea and vomiting as many as 66 people (85.7%). The incidence of PONV in patients with SC ERACS method at Hermina Hospital Padang in September-October 2023 was found to be degree 0 or no nausea and vomiting as many as 66 people (85.7%) with the characteristics of the most ERACS SC patients aged 20-35 years, no previous history of PONV, and multiparous.